Changes in N6-Methyladenosine Modification Modulate Diabetic Cardiomyopathy by Reducing Myocardial Fibrosis and Myocyte Hypertrophy - Ju, Wenhao; Liu, Kai; Ouyang, Shengrong; Liu, Zhuo; He, Feng; Wu, Jianxin (Frontiers in Cell and Developmental Biology, 2021)
In this study, we aimed to systematically profile global RNA N6-methyladenosine (m6A) modification patterns in a mouse model of diabetic cardiomyopathy (DCM). Patterns of m6A in DCM and normal hearts were analyzed via m6A-specific methylated RNA immunoprecipitation followed by high-throughput sequencing (MeRIP-seq) and RNA sequencing (RNA-seq). m6A-related mRNAs were validated by quantitative real-time PCR analysis of input and m6A immunoprecipitated RNA samples from DCM and normal hearts. A total of 973 new m6A peaks were detected in DCM samples and 296 differentially methylated sites were selected for further study, including 106 hypermethylated and 190 hypomethylated m6A sites (fold change (FC) > 2, p < 0.05). Gene ontology and KEGG Pathway analyses indicated that unique m6A-modified transcripts in DCM were closely linked to cardiac fibrosis, myocardial hypertrophy, and myocardial energy metabolism. Total m6A levels were higher in DCM, while levels of the fat mass and obesity-associated (FTO) protein were downregulated. Overexpression of FTO in DCM model mice improved cardiac function by reducing myocardial fibrosis and myocyte hypertrophy. Overall, m6A modification patterns were altered in DCM, and modification of epitranscriptomic processes, such as m6A, is a potentially interesting therapeutic approach.